2018
DOI: 10.1002/ncp.10064
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Coding, and Reimbursement of Pediatric Malnutrition at an Urban Academic Medical Center

Abstract: Malnutrition coding may have a significant financial impact and processes improvement efforts can be made to improve malnutrition coding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Malnutrition was found to be prevalent in 30% of pediatric inpatients in a single-center study in the United States; however, only 33% of malnourished patients were given a malnutrition-related ICD-10 code at discharge. A reimbursement calculation showed that coding for malnutrition resulted in an additional cost of US$27,664.70 to the hospital in 2 years [ 9 ]. Therefore, the true prevalence of nutritional disorders from ICD-10-CM codes was possibly underrepresented.…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition was found to be prevalent in 30% of pediatric inpatients in a single-center study in the United States; however, only 33% of malnourished patients were given a malnutrition-related ICD-10 code at discharge. A reimbursement calculation showed that coding for malnutrition resulted in an additional cost of US$27,664.70 to the hospital in 2 years [ 9 ]. Therefore, the true prevalence of nutritional disorders from ICD-10-CM codes was possibly underrepresented.…”
Section: Discussionmentioning
confidence: 99%
“…Thus malnutrition remains underrecognized, underdiagnosed, and underdocumented [7,11]. This compromises not only the patient's treatment and, consequently, clinical outcomes but also the scores of ROM and SOI, increasing the unclaimed potential reimbursement as a result of the lack of malnutrition diagnosis in the medical records [7,11,12,42].…”
Section: Discussionmentioning
confidence: 99%
“…The International Classification of Disease, 10th Edition (ICD-10) codes 44.1 (mild protein malnutrition), E44.0 (moderate protein/calorie malnutrition), and E43.0 (severe protein/calorie malnutrition) should be used when appropriate. 4 The steps outlined above will enable the malnutrition diagnosis to be added to the All Patient Refined-Diagnosis Related Group (APR-DRG) payment methodology for that patient and that admission, thereby potentially increasing the actual hospital reimbursement. Furthermore, malnutrition impacts the severity of illness and risk of mortality scores, which can influence the hospital's performance on required quality-reporting dashboards and have downstream influences on reimbursement.…”
Section: How Does Billing and Reimbursement Work In The Neonatal Intensive Care Unit? Does The Rdn's Diagnosis Of Malnutrition Impact Thementioning
confidence: 99%